2011
DOI: 10.1097/fjc.0b013e31820d1c54
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiovascular Drug Trials, Lessons Learned

Abstract: Few drugs have been labeled for pediatric cardiovascular indications and many children with cardiac disease are prescribed drugs off-label. Recent initiatives have narrowed this gap and as a result there are an increasing number of cardiology trials in the pediatric population. Many studies, however, have either failed to show a dose response in children or have not shown efficacy in children when they have established efficacy in adults. Clinical trials are challenging in children; many factors such as lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…The challenge encountered with these conditions is that the pathophysiology is often less well-understood and pediatric validated clinical endpoints are often lacking. 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…The challenge encountered with these conditions is that the pathophysiology is often less well-understood and pediatric validated clinical endpoints are often lacking. 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…Although there may be a lower cost associated with small individual trials, it is possible that if resources were instead directed toward large trials aimed at answering the most important questions, more useful evidence could be generated without increasing total costs. [1][2][3] Third, it is noteworthy that the distribution of trials with regard to therapeutic area seems to generally mirror overall disease burden in children, and there is a higher percentage of trials focused on disease prevention in children. There have been concerns that trials in children may not reflect disease burden because of financial incentives in place for the pharmaceutical industry in the Pediatric Exclusivity Provision to study drugs with a large adult market.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several questions have been raised regarding the conduct of clinical trials in children, including how best to prioritize and stimulate research in the areas of greatest clinical need, funding and regulatory issues, and the globalization of research. [1][2][3] In addition, the general underrepresentation of children in clinical research and the limited pediatric evidence-base has lead to several recent federal initiatives aimed at stimulating research in children, beginning with the Pediatric Exclusivity Provision in 1997. [4][5][6] However, it has been difficult to assess the current status of the clinical trial enterprise as a whole, both in terms of characterizing the overall scope of trials being performed and describing changes over time.…”
mentioning
confidence: 99%
“…It is also often true, as in this case, that new therapies become widely adopted into routine pediatric practice, based on extrapolation from adults or small pediatric studies, making conducting more rigorous large-scale studies difficult due to the lack of clinical equipoise. 20 However, more recent analyses of large data sets have shown that there is in fact widespread variation in the way corticosteroids are used in this setting, and have questioned the clinical benefit associated with corticosteroids. 1,6 These data support the feasibility and necessity of a large randomized trial.…”
Section: Discussionmentioning
confidence: 99%